3D numerical modeling of liquid metal turbulent flow in an annular linear induction pump. (January 2018) - Abdullina, K.I.; Bogovalov, S.V.; Zaikov, Yu.P.
Highlights: 3D numerical simulation of the liquid metal flow in the MHD pumps is performed. ANSYS/EMAG and ANSYS/CFX is modified and unified into a program complex. The effect of the flow on the electromagnetic field is taken into account. The verification of the code is performed on a test problem. The performance curve and efficiency for different flow rates are obtained. Abstract: 3D numerical simulation of the liquid metal flow affected by electromagnetic field in the Annular Linear Induction Pump (ALIP) is performed using modified ANSYS package. ANSYS/EMAG has been modified to take into account arbitrary velocity field at the calculation of the electromagnetic field and has been unified with CFX to provide integration of all the system of ​magnetohydrodynamic (MHD) equations defining dynamics of the conductive media in the variable electromagnetic field. The non-stationary problem is solved taking into account the influence of the metal flow on the electromagnetic field. The pump performance curve and the dependence of the pump efficiency on a flow rate are obtained.